Methodology for determining the parameters of high-temperature superconducting power transformers with current limiting function - Vadim Zinovievich Manusov; Dmitriy Mihailovich Ivanov; Arseniy Valerievich Semenov; Gennady Viktorovich Ivanov (Institute of Advanced Engineering and Science, 2023)
This paper substantiates a new adaptive method for determining parameters of high-temperature superconducting power transformers with current limiting function. The main focus is the design of current-limiting superconducting windings in the light of new restrictions on current density, magnetic induction, critical current and critical temperature. The presented method considers the nature of alternating current (AC) losses in a superconductor under nominal operating conditions, features of the dielectric medium (liquid nitrogen), as well as the reduced values of the short-circuit voltage (0.5 to 1.5%). The main design features of high-temperature superconducting (HTS) transformers are specified, and a prototype of a three-phase HTS transformer of 63 kVA with a short-circuit current limiting function is developed. It is shown that HTS units have some advantages over conventional transformers: a 90 to 95% active losses reduction, short-circuit current limitation function, explosion and fire safety, a 60% reduction in weight and size, and increased efficiency (up to 99.8%). Experimental studies confirm that the short-circuit current limitation function is safe and efficient. It is demonstrated that during the short-circuit current limitation, significant heat flows occur on the windings, which should not exceed the critical value above which the superconductor could not return to the superconducting state by itself.